Survival and direct axes formation of Eucheuma denticulatum (Rhodophyta) in tissue culture under ambient condition. - Moquera, Gyll Ann Marie L.; Institute of Aquaculture (2023.)
Seaweed growth and survival are highly dependent on abiotic factors, including temperature, irradiance, carbon dioxide, and nutrients. For maximum growth and survival, laboratories set ideal conditions to meet optimum requirements; however, this can be expensive and may require high operating costs. This study aimed to test the survival and direct axes formation of Eucheuma denticulatum in tissue culture under ambient condition. Sections of E. denticulatum (3-5 mm, 1 segment: 10 mL) were cultured at ambient and controlled conditions of temperature and irradiance, with and without seaweed extract (Ascophyllum marine plant extract powder; AMPEP), respectively, for 45 days. Results revealed that seaweeds grown under ambient condition did not survive throughout the culture period, regardless of AMPEP enrichment. Algal explants, mostly from AMPEP treatment, showed signs of tissue bleaching and disintegration as early as day 7. Diurnal temperature fluctuations (25-31°C) and low irradiance (5-7 μmol photons m-2 s-1) may have contributed to the mortality of E. denticulatum in this culture condition. Whereas samples cultured under controlled irradiance (50-100 μmol photons m-2 s-1) and temperature (23-24°C) had survival rates of 99.80% and 99.35%, with and without AMPEP treatment, respectively. Seaweeds treated with AMPEP had higher direct axes formation (95.95%) and longer shoot length (2.41 mm) than those without AMPEP (81.60%, 1.98 mm). Overall, this study presents the inefficacy of seaweed tissue culture under ambient condition, and so suggests the use of controlled growth environment for the mass propagation of E. denticulatum explants.
Thesis (Undergraduate, Bachelor of Science in Fisheries) College of Fisheries and Ocean Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2023
Keywords: Rhodophyta; Eucheuma denticulatum